2003
DOI: 10.1097/00008571-200304000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of attention and response to therapy in dementia by butyrylcholinesterase

Abstract: These findings indicate that the butyrylcholinesterase enzyme is a major regulator of attention especially in cholinergic deficiency states through its ability to hydrolyse acetylcholine. Pharmacologic manipulation of this enzyme may be a viable strategy in dementia treatment and, with butyrylcholinesterase genotyping, may provide pharmacogenomic treatment of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 28 publications
1
50
1
Order By: Relevance
“…33 Moreover, in a predominantly dementia with Lewy bodies cohort, the BCHE-K variant is associated with enhanced attention at baseline and poorer response to rivastigmine treatment, compared with those who did not carry the K variant and had impaired attention at baseline. 32 Disease progression in those with the K variant was only 60% of that seen in the wild-type group. 32 Another study found that in severe AD, as defined by an MMSE p8, the rate of cognitive decline was lower in those subjects with the K variant.…”
Section: Apoe Bche and Chei Treatment Response In Admentioning
confidence: 99%
See 3 more Smart Citations
“…33 Moreover, in a predominantly dementia with Lewy bodies cohort, the BCHE-K variant is associated with enhanced attention at baseline and poorer response to rivastigmine treatment, compared with those who did not carry the K variant and had impaired attention at baseline. 32 Disease progression in those with the K variant was only 60% of that seen in the wild-type group. 32 Another study found that in severe AD, as defined by an MMSE p8, the rate of cognitive decline was lower in those subjects with the K variant.…”
Section: Apoe Bche and Chei Treatment Response In Admentioning
confidence: 99%
“…32 Disease progression in those with the K variant was only 60% of that seen in the wild-type group. 32 Another study found that in severe AD, as defined by an MMSE p8, the rate of cognitive decline was lower in those subjects with the K variant. 46 This study found significantly better late cognitive response in BCHE-K carriers in moderate-to-severe disease (MMSE p15) ( Table 6).…”
Section: Apoe Bche and Chei Treatment Response In Admentioning
confidence: 99%
See 2 more Smart Citations
“…The BuChE-K variant (Ala539Thr) is present in some 33% of Caucasian and Asian individuals, and those possessing two alleles for BuChE-K (homozygous) show an approximate 30% reduced BuChE activity (Bartels et al 1992;Ballard et al 2005). In an increasing number of studies where AD subjects were genotyped for BuChE genetic variants and their disease progression measured (O'Brien et al 2003;Holmes et al 2005;Ballard et al 2005;Déniz-Naranjo et al 2007), those with BuChE deficiency had a delayed onset of AD and a slower cognitive decline compared to patients with wild-type BuChE levels. The choice of which cymserine analogue to finally translate to clinical assessment will ultimately depend on the cost of bulk synthesis and tolerability in cellular and animal models.…”
Section: Discussionmentioning
confidence: 99%